DEVELOPMENT OF MELATIK: INTERACTIVE LEARNING MULTIMEDIA TO ENHANCE STUDENTS' MOTIVATION AND LEARNING OUTCOMES IN INFORMATICS EDUCATION - Syamsudin, Enang; Rahmadonna, Sisca (Research and Development Journal of Education, 2025)
This research aims to (1) develop ICT learning multimedia for class X Senior High School/Madrasah Aliyah students, (2) assess its feasibility and practicality, and (3) examine its effectiveness in enhancing students' motivation and learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) and the MDLC approach (Multimedia Development Life Cycle). The research was conducted at Madrasah Aliyah Ma'arif Cilacap Tengah, involving class X-1 as the experimental group and class X-2 as the control group. Data collection methods included interviews, observations, questionnaires, and learning outcome tests, analyzed using qualitative and quantitative descriptive techniques. The results showed that: (1) ICT learning multimedia is highly feasible based on media expert validation (3.72, "very feasible") and material expert validation (3.79, "very feasible"); (2) its practicality was rated "very practical" with average scores of 3.50 in the initial trial and 3.41 in the field test; and (3) its effectiveness is demonstrated by an increase in student motivation (n-gain = 0.53, "medium") and improved learning outcomes in the experimental class (n-gain = 0.81, "high"). Thus, this multimedia has proven effective in enhancing motivation and learning outcomes among students at Madrasah Aliyah Ma'arif Cilacap Tengah.